Thromboprophylaxis of cancer patients undergoing systemic therapy in the ambulatory setting. Issue 1 (March 2022) - Ciuffini, L.A.; Wang, T.F.; Lodigiani, C.; Carrier, M.
Abstract: Cancer-associated Thrombosis (CAT) is a common complication among patients with cancer which is associated with significant morbidity and mortality. The risk of CAT varies widely depending on cancer types and treatments and its cumulative incidence increases over time. Although patients with cancer have a high risk of developing venous thromboembolism, pharmacological thromboprophylaxis is not routinely recommended for ambulatory patients receiving chemotherapy but is suggested for those deemed as high-risk. Risk assessment models can help clinicians identify ambulatory patients at high risk who would most benefit from thromboprophylaxis with low molecular weight heparin or direct oral anticoagulants (apixaban or rivaroxaban). This narrative review will summarize the data on pharmacological thromboprophylaxis in ambulatory patients with cancer, provide further insights into the safety and efficacy of different anticoagulants, and suggest implementation methods using a multidisciplinary approach leading to an optimization of preventative strategies in this patient population.